Question not found

Not a good answer? Get an answer now. (Free)

Rating

There are no new answers.

A plant without enough water may wilt and close its stomata (leaf openings). This decreases the rate of photosynthesis because _____.
chloroplasts don't have access to the sunlight
carbon dioxide can't be absorbed
nutrients from the soil can't be absorbed **Weegy:** A plant without enough water may wilt and close its stomata (leaf openings). This decreases the rate of photosynthesis because chloroplasts don't have access to the sunlight.
(More)

Question

Expert Answered

Asked 6/20/2013 10:27:24 AM

0 Answers/Comments

Subtract -2k3 + k2 - 9 from 5k3 - 3k + 7.
3k3+ k2- 3k - 2
-7k3+ k2+ 3k - 16
7k3- k2- 3k + 16 **Weegy:** 5k3 - 3k + 7-(-2k3 + k2 - 9)=> 5k3 - 3k + 7+2k3-k2+9==> 5k3+2k3-k2-3k+7+9 ==> 7k3-k2-3k+16 ....Hence your answer is 7k3- k2- 3k + 16
**User:** Simplify (2n + 5) - (3n + 7) + (4n - 9).
-3n - 11
3n - 11
-3n + 11
3n + 11 **Weegy:** Simplify (2n + 5) - (3n + 7) + (4n - 9).
ANSWER: 3n - 11
**User:** Simplify a - {b - [c - (d - e) - f] - g}.
a + b + c - d + e - f + g
a - b + c - d + e - f + g
a + b + c + d + e - f + g
a - b + c - d + e + f - g **User:** Simplify 5t + (t - 3) - [(7t + 5) - (8 - 3t)].
-4t
4t
-10t
10t **Weegy:** (a)-4t is the answer. 5t + (t - 3) - [(7t + 5) - (8 - 3t)] = -4t **User:** Using the polynomials Q = 3x2 + 5x - 2, R = 2 - x2, and S = 2x + 5, perform the indicated operation.
Q - [R + S]
2x2+ 3x- 9
4x2- 3x+ 9
2x2- 3x+ 9
4x2+ 3x- 9 **Weegy:** D. 5x - 4 is the answer. **User:** Simplify 5 + 2{x - 4[3x + 7(2 - x)]}.
-34x - 107
34x - 107
34x + 107 **Weegy:** (a)34x - 107 or x = 107/34 **User:** Select the correct product.
(x2 + 4x + 8)(2x - 1)
2x3+ 7x2+ 12x- 8
2x3- 7x2- 12x- 8
x2+ 6x+ 7
x2+ 8x- 8 **Weegy:** The correct answer to the presented problem is (a) 2x3 + 7x2 + 12x - 8 **User:** Select the correct product.
(6 - d)(d2 - 5 + 3d)
6d2- 30d
d3- 3d2- 23d+ 30
d2+ 2d- 30
-d3+ 3d2+ 23d- 30 **Weegy:** 6d2- 30d d3- 3d **User:** Select the correct product.
(y + z)3
y3+z3
y3+ 3y2z+ 3yz2+z3
3y+ 3z
y3z3 **Weegy:** (x+y)?=x?-2x?y+y?x-x?y+2xy?-y? (More)

Question

Updated 6/22/2014 7:39:25 PM

4 Answers/Comments

5t + (t - 3) - [(7t + 5) - (8 - 3t)]

= 5t + t - 3 - (7t + 5 - 8 + 3t)

= 6t - 3 - (10t - 3)

= 6t - 3 - 10t + 3

= -4t

= 5t + t - 3 - (7t + 5 - 8 + 3t)

= 6t - 3 - (10t - 3)

= 6t - 3 - 10t + 3

= -4t

Added 6/22/2014 7:21:01 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by andrewpallarca [6/22/2014 7:26:02 PM]

5 + 2{x - 4[3x + 7(2 - x)]}

= 5 + 2[x - 4(3x + 14 - 7x)]

= 5 + 2[x - 4(14 - 4x)]

= 5 + 2(x - 56 + 16x)

= 5 + 2(17x - 56)

= 5 + 34x - 112

= 34x - 107

= 5 + 2[x - 4(3x + 14 - 7x)]

= 5 + 2[x - 4(14 - 4x)]

= 5 + 2(x - 56 + 16x)

= 5 + 2(17x - 56)

= 5 + 34x - 112

= 34x - 107

Added 6/22/2014 7:24:22 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by andrewpallarca [6/22/2014 7:26:18 PM]

(6 - d)(d^2 - 5 + 3d)

= 6d^2 - 30 + 18d - d^3 + 5d - 3d^2

= - d^3 + (6d^2 - 3d^2) + (18d + 5d) - 30

= - d^3 + 3d^2 + 23d - 30

= 6d^2 - 30 + 18d - d^3 + 5d - 3d^2

= - d^3 + (6d^2 - 3d^2) + (18d + 5d) - 30

= - d^3 + 3d^2 + 23d - 30

Added 6/22/2014 7:29:49 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by andrewpallarca [6/22/2014 7:40:16 PM]

(y + z)^3 = y^3+ 3y^2z+ 3yz^2+z^3

Added 6/22/2014 7:39:25 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by andrewpallarca [6/22/2014 7:41:46 PM]

Select the correct product.
(2x + 9)(x + 1)
2x2+ 11x+ 9
3x2+ 11x+ 9
2x2- 7x+ 9
2x2+ 11x+ 10 **Weegy:** Can you clarify your question please? **User:** Select the correct product.
(2x + 9)(x + 1)
2x2+ 11x+ 9
3x2+ 11x+ 9
2x2- 7x+ 9
2x2+ 11x+ 10 **Weegy:** Can you clarify your question please? **User:** Select the correct product.
(a + 8)(b + 3)
ab+ 8a+ 3b+ 24
ab+ 3a+ 8b+ 24
11ab
24ab **Weegy:** ab+3a+8b+24 is the answer. **User:** Select the correct product.
(j + 7)(k - 5)
-35jk
jk- 12jk- 35
jk- 5j+ 7k- 35
7j- 5k **Weegy:** (j + 7)(k - 5), the product is jk- 5j+ 7k- 35 **User:** Find the product.
(n + 7)2
2n² + 14n + 49
n² + 14n + 14
n² + 14n + 49 **Weegy:** (n + 7)(n + 7), the product is n² + 14n + 49
**User:** Find the product.
(r + s)2
r² + 2rs + s
r² + 2rs + s²
r² + 2rs + 2s² **Weegy:** (r + s)^2, the product is r² + 2rs + s² (More)

Question

Expert Answered

Updated 6/20/2013 12:53:27 PM

1 Answer/Comment

(2x + 9)(x + 1)

= 2x^2 + 9x + 2x + 9

= 2x^2 + 11x + 9

= 2x^2 + 9x + 2x + 9

= 2x^2 + 11x + 9

Added 6/20/2013 12:53:27 PM

Find the product mentally.
(ab + 3)(ab - 3)
a2b2+ 9
a2b2- 6ab- 9
a2b2- 9

Question

Not Answered

Updated 6/20/2013 12:41:30 PM

1 Answer/Comment

(ab + 3)(ab - 3)

= a^2b^2 + 3ab - 3ab - 9

= a^2b^2 - 9

= a^2b^2 + 3ab - 3ab - 9

= a^2b^2 - 9

Added 6/20/2013 12:41:30 PM

This answer has been added to the Weegy Knowledgebase

Find the product mentally.
(2m - 9)2
2m2- 18m+ 81
2m2- 81m+ 81
4m2- 36m+ 81

Question

Not Answered

Updated 6/20/2013 12:48:54 PM

1 Answer/Comment

(2m - 9)^2

= 4m^2 - 18m + (-18m) + 81

= 4m^2 - 36m + 81

= 4m^2 - 18m + (-18m) + 81

= 4m^2 - 36m + 81

Added 6/20/2013 12:48:54 PM

This answer has been added to the Weegy Knowledgebase

25,792,924 questions answered

There are no comments.